Analysis of Volatile Compounds with Odor Characteristics in Dianhong, Chuanhong, and Keemunhong Based on SPME-GC×GC-MS - Sinuo Li; Qi Meng; Chunli Huang; Peihan Zhou; Sirui Yao; Yamin Guo; Xiaojun Wang (Molecules)
China is the place of origin and main producer of black tea worldwide, with Dianhong (DH), Chuanhong (CH), and Keemunhong (KH) being the famous Chinese black teas. The contents of various odor components in black teas differ with their origins. However, the effects of these differences on the presentation of distinctive odor characteristics in various products remain unclear. We aimed to elucidate the odor characteristics and odor compounds of these three black teas; to this end, we performed a sensory evaluation and multivariate statistical analysis based on comprehensive two-dimensional gas chromatography–mass spectrometry (GC×GC-MS) results. The sensory evaluation revealed that the odor characteristics of DH were floral and fruity, whereas sweet and herbal-like odors were more intense in CH and QH. A total of 119 volatile compounds were detected, with alcohols, aldehydes, and esters being the main volatile compounds. Among them, 41 volatile compounds were identified with an odor activity value (OAV) of >1, and 24 of them were selected through principal component analysis, hierarchical cluster analysis, and orthogonal partial least squares discriminant analysis as marker substances to distinguish the three teas; thus, 24 volatile compounds are important odor compounds of DH, CH, and QH.